Financial Literacy, Attitude, Internal Control Locus, and Money-Associated Behavior of Undergraduate Students - Oktavianus Marbun; Bram Hadianto; Ana Mariana (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2023)
Financial literacy becomes the guideline for its users to perform financially well. As educated users, undergraduate business students are expected to behave well in managing their money. Furthermore, to test this tendency, this study employs the financial attitude and internal control locus as additional determinants. This research also takes 150 students in the management department of business faculty at Maranatha Christian University as a population. Considering some batches utilized, this study employs stratified random sampling to take the samples. Besides, this study uses a survey method to obtain their response related to demographic and academic features, covariance-based structural equation model, and the related statistic: the probability of critical ratio to analyze the data and examine the first, second, and third hypotheses. After testing them, this investigation concludes that the more financially literate the students are, the more they behave financially. With a better financial attitude and internal control locus, the students can manage their money well.